Posterior circulation collaterals as predictors of outcome in basilar artery occlusion: a sub-analysis of the BASICS randomized trial - Lima, Fabricio O.; Rocha, Felipe A.; Silva, Henrique C.; Puetz, Volker; Dippel, Diederik; van den Wijngaard, Ido; Majoie, Charles; Yoo, Albert J.; van Zwam, Wim; de Lucena, Adson F.; Bandeira, Diego De Almeida; Arndt, Martin; et al. (Frontiers in Neurology, 2024)
Introduction and purpose Basilar artery occlusion (BAO) is still one of the most devastating neurological conditions associated with high morbidity and mortality. In the present study, we aimed to assess the role of posterior circulation collaterals as predictors of outcome in the BASICS trial and to compare two grading systems (BATMAN score and PC-CS) in terms of prognostic value. Methods We performed a sub-analysis of the BASICS trial. Baseline clinical and imaging variables were analyzed. For the imaging analysis, baseline CT and CTA were analyzed by a central core lab. Only those patients with good or moderate quality of baseline CTA and with confirmed BAO were included. Multivariable binary logistic regression analysis was used to test the independent association of clinical and imaging characteristics with a favorable outcome at 3 months (defined as a modified Rankin Score of ≤3). ROC curve analysis was used to assess and compare accuracy between the two collateral grading systems. Results The mean age was 67.0 (±12.5) years, 196 (65.3%) patients were males and the median NIHSS was 21.5 (IQR 11–35). Median NCCT pc-ASPECTS was 10 (IQR10-10) and median collateral scores for BATMAN and PC-CS were 8 (IQR 7–9) and 7 (IQR 6–8) respectively. Collateral scores were associated with favorable outcome at 3 months for both BATMAN and PC-CS but only with a modest accuracy on ROC curve analysis (AUC 0.62, 95% CI [0.55–0.69] and 0.67, 95% CI [0.60–0.74] respectively). Age (OR 0.97, 95% CI [0.95–1.00]), NIHSS (OR 0.91, 95% CI [0.89–0.94]) and collateral score (PC-CS – OR 1.2495% CI [1.02–1.51]) were independently associated with clinical outcome. Conclusion The two collateral grading systems presented modest prognostic accuracy. Only the PC-CS was independently associated with a favorable outcome at 3 months.